Efficient Biometric Indexing and Retrieval Techniques for Large-Scale Systems - Kavati, Ilaiah; Prasad, Munaga V. N. K; Bhagvati, Chakravarthy (SpringerBriefs in Computer Science, 2017)
This work presents a review of different indexing techniques designed to enhance the speed and efficiency of searches over large biometric databases. The coverage includes an extended Delaunay triangulation-based approach for fingerprint biometrics, involving a classification based on the type of minutiae at the vertices of each triangle.